Foreword, Swine Day 2025 (Kansas Agricultural Experiment Station Research Reports, 2025)
This file includes the 2025 Swine Day Research Report introduction, standard abbreviations, K-State Vitamin and Trace Mineral Premixes statement, biological variability and chances of error explanation, and acknowledgments of our supporters. We hope that the information in the 2025 Swine Day Research Report will be of benefit as we attempt to meet the needs of the Kansas swine industry.
Keywords: Kansas State University swine research; swine; sows; nursery pigs; finishing pigs; feed safety; swine health; disease management; nutrition